Repositioning of Antiparasitic Drugs for Tumor Treatment - Li, Yan-Qi; Zheng, Zhi; Liu, Quan-Xing; Lu, Xiao; Zhou, Dong; Zhang, Jiao; Zheng, Hong; Dai, Ji-Gang (Frontiers in Oncology, 2021)
Drug repositioning is a strategy for identifying new antitumor drugs; this strategy allows existing and approved clinical drugs to be innovatively repurposed to treat tumors. Based on the similarities between parasitic diseases and cancer, recent studies aimed to investigate the efficacy of existing antiparasitic drugs in cancer. In this review, we selected two antihelminthic drugs (macrolides and benzimidazoles) and two antiprotozoal drugs (artemisinin and its derivatives, and quinolines) and summarized the research progresses made to date on the role of these drugs in cancer. Overall, these drugs regulate tumor growth via multiple targets, pathways, and modes of action. These antiparasitic drugs are good candidates for comprehensive, in-depth analyses of tumor occurrence and development. In-depth studies may improve the current tumor diagnoses and treatment regimens. However, for clinical application, current investigations are still insufficient, warranting more comprehensive analyses.